Antibacterial activity of erythrocyte from grass carp (Ctenopharyngodon idella) is associated with phagocytosis and reactive oxygen species generation. Issue 92 (September 2019) - Qin, Zhendong; Vijayaraman, Sarath Babu; Lin, Hanzuo; Dai, Yunjia; Zhao, Lijuan; Xie, Jungang; Lin, Weiqiang; Wu, Zaohe; Li, Jun; Lin, Li
Abstract: Red blood cells (RBCs) are widely accepted as their primary function in respiration. Recent studies in mammals have revealed a vital role in immune responses of RBCs; however, little is known about immune function of teleost erythrocytes. Here we demonstrated that RBCs from grass carp ( Ctenopharyngodon idella ) were capable of binding and aggregating the bacteria with apparent morphological alterations. The phagocytosis by teleost RBCs (erythrophagocytosis) was visualized by confocal, scanning and transmission electron microscopy. Hb-Fe II of hemoglobin (Hb) could quickly be auto-oxidated to Hb-Fe III (methemoglobin/metHb) in the presence of oxygen (O2 ), and release superoxide radical (O2 −. ) which could be spontaneously dismutated into H2 O2 that could further oxidize Hb-Fe III to transient HbFe IV -OH (ferryl-Hb). Furthermore, bacterial extracellular proteases and pathogen-associated molecular patterns (PAMPs) binding to Hb could synergistically activate pseudoperoxidase, subsequently facilitated the generation of reactive oxygen species (ROS) which were toxic to the bacteria. Our results indicated that erythrocyte pertains anti-bacterial activity using unique ROS generation pathway via oxidation of hemoglobin and associated with its phagocytosis. Highlights: Grass carp erythrocytes were capable of binding and aggregating the pathogens. Extensive phagocytic activity towards the pathogens was observed in Grass carp erythrocytes. The haemoglobin (Hb) were auto-oxidated when exposed to open air and released potentially toxic superoxide radicals. The PAMPs and protease from pathogens together able to stimulate the Hb to release superoxide radicals.